Sexual Harassment Hostile Environment: An Occupational Safety And Health Legal Implications - Rahim, Rohani Abdul; Fandi, Fieza Fazlin; Landa, Azizah; Intung, Rovina; Hassan, Maria (Universiti Sains Malaysia, 2016)

(untitled)
In legal terms, sexual harassment is any unwelcome sexual advance or conduct that intimidate, hostile, or offensive to the work environment. In fact, sexual harassment ranges from repeated offensive or belittling jokes to a workplace full of offensive pornography (creating a hostile work environment) to sexual assault. Most often sexual harassment takes the form of men harassing women, but it can also be conducted onto men and between sexes. Superiors or coworkers who discriminate employee on basis of sex can be a form of sexual harassment when the act is not welcome by the employee. Sex discrimination is prohibited in every aspect of the employment relationship, from hiring, interviewing, and starting salaries to promotions, benefits, job responsibilities, firings, and layoffs. In Malaysia, sexual harassment can be seen as civil and criminal offences depending on what are the victim claims. As an employee the employment Act 1955 (amendment 2012) provide some improvements to Sexual harassment prevention at workplace. Complaint relating to sexual harassment can be made (i) by an employee against another employee; (ii) by an employee against any employer; or (iii) by an employer against an employee. These provision place a duty not only on the employer but the Director General and Minister of Human Resources to conduct enquiry into the Sexual harassment allegation. This paper will dwell on (a) the sexual harassment that cause the hostile environment, such as sexual discrimination and offensive pornography; (b) to determine how women become victimize (c) complaint procedures to prevention of sexual harassment at workplaces and, (d) the legal and economic implications because of the sexual harassment conducted on the victims.